The Relationship Between Body Image and Self-Confidence Among University Students in Yogyakarta - Maulida, Faza; Astuti, Yulianti Dwi (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: This research aims to know the relationship between body image and self-confidence of college students in Yogyakarta. Research Methods: Researchers conducted data retrival using scale of self-confidence made by researcher based on Lauster’s theory (Gufron & Risnawita, 2014) while the body image scale are made by researcher based on Thmpson’s theory (2000). Subjects in this research were 211 college students in Yogyakarta. Finding/Results: From the result of a test of correlation it was found there is a significance correlation between body image with self-confidence (p<0,05) with value of significance p=0,000. The coefficient correlation (r) of the hypothesis is 0,483, which indicate a positive relationship between these two variabels. Conclusion: This research concludes by offering suggestions to improve the effectiveness of educational planning and implementation at SDUT Masyitoh Muslimat NU Bandungrejo, thereby contributing to improved outcomes for students and the institution as a whole.